Pandangan Ibn Taimiyah Tentang Konsep Ibadah dan Muamalah (Tinjauan Normatif dan Historis Sosiologis) - Ni'man Samad; Kurniati; Misbahuddin (CV. Lenggogeni Data Publishing, 2023)
Ibn Taymiyyah is known as the inspiration of the Wahhabi movement that aims to the purification of the teachings of Islam. This movement departs from the separation between the ‘ubūdiyyah and un-‘ubūdiyyah teachings, which are also inspired by Ibn Taymiyyah's thought. In 'ibādah, Ibn Taymiyyah holds the rule that as long as there is no ordered argument it should not be done. However, the notion of ibādah according to Ibn Taymiyyah is not limited to mahdlah worship but more broadly. Whereas in mu'āmalah, he holds the rule of allowing doing anything as long as there is no prohibition against it. In shaping the concept of 'ibādah and mu'āmalah, at first, Ibn Taymiyyah accepted it as something normative from the thought of Ahmad ibn Hanbal. But when he saw the social reality with the number of deviations' in ibādah done by Muslims, the concept that has been obtained normatively from the thought of Ahmad ibn Hanbal is reaffirmed and expanded to become a sociological concept, in addition to being normative.